Examining relationships between home-based shared book reading practices and children's language/literacy skills at kindergarten entry. Issue 13 (10th November 2019) - Anderson, Kimberly L.; Atkinson, Terry S.; Swaggerty, Elizabeth A.; O'Brien, Kevin
ABSTRACT: At start-up of a book distribution programme (Dolly Parton's Imagination Library) in a southeastern United States community, we examined baseline relationships between at-home shared book reading (SBR) and children's language/literacy abilities and skills at kindergarten entry. One hundred fifty-two parent/child dyads participated; children (53% male) had a mean age of 5 years, 6 months. Survey data included family demographics, SBR frequency and practices, and children's interest in reading. Household income and parent education level were positively associated with SBR frequency. Relationships between SBR frequency and children's performance on measures of print concepts/ reading behaviours, narrative retelling, narrative comprehension, and interest in reading were statistically significant. Performance on a letter naming fluency and phonemic segmentation measure was significantly related to the SBR practice of stopping to ask the child about letters or words but not to SBR frequency. Differential associations are discussed in terms of constrained and unconstrained abilities and skills, with implications for future research.